Guidance and Counseling Management Concepts in Education Student Character - Windi Ayu Fitria; Muhammad Rezza Septian (Study Program Guidance and Counseling, Univesitas Pendidik, 2024)
Abstract: The Guidance and Counseling service process at school plays a very important role in developing student character. This activity must begin with planning guidance and counseling activities by analyzing the needs of students. A counselor, specifically a guidance and counseling teacher, must have good management (management and regulation) in order to have good steps in implementing the program that will be created. Guidance and counseling teachers need to design annual, semi-annual, monthly, weekly and even daily programs and for the program to run it is necessary to adapt it to the functions of management, it must truly achieve the ideal functions of implementation, organizing, executing, supervising. In character education, students are expected to be more confident, disciplined, have a high social spirit, be honest, respect each other and many other positive student behaviors. Keywords : Management Concepts, Guidance and Counseling, Student Character